2021
DOI: 10.52549/ijeei.v9i4.3432
|View full text |Cite
|
Sign up to set email alerts
|

Distribution network reconfiguration considering DGs using a hybrid CS-GWO algorithm for power loss minimization and voltage profile enhancement

Abstract: This paper presents an implementation of the hybrid Cuckoo search and Grey wolf (CS-GWO) optimization algorithm for solving the problem of distribution network reconfiguration (DNR) and optimal location and sizing of distributed generations (DGs) simultaneously in radial distribution systems (RDSs). This algorithm is being used significantly to minimize the system power loss, voltage deviation at load buses and improve the voltage profile. When solving the high-dimensional datasets optimization problem using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…There are several optimal network reconfiguration approaches available in literature. Those that closely relate to the present study are reported in [3]- [8]. Just as it is the case in the present study, these works consider load variations.…”
Section: Introductionsupporting
confidence: 74%
“…There are several optimal network reconfiguration approaches available in literature. Those that closely relate to the present study are reported in [3]- [8]. Just as it is the case in the present study, these works consider load variations.…”
Section: Introductionsupporting
confidence: 74%
“…Table IV compares the performance of the developed SSAbased approach against approaches based on Grasshopper Optimization Algorithm (GOA) [6], Hybrid Cuckoo Search-Grey Wolf Optimization algorithm (CSA-GWO) [3] and the Modified Sequential Switch Opening and Exchange (MSSSOE) [7] method. It can be noted from Table IV that, for both nominal (100%) and heavy (160%) load conditions, the developed SSA-based approach outperformed GOA, CSA-GWO, and MSSOE based approaches in terms of total power losses (both real and reactive) reduction and the improvement in bus voltages.…”
Section: A Test Case 1: Ieee 33-bus Radial Distribution Systemmentioning
confidence: 99%
“…Kaberere 1 and G.K. Irungu 2 are with the Department of Electrical and Electronic Engineering, Jomo Kenyatta University of Agriculture and Technology (JKUAT), Nairobi, Kenya (e-mail 1 : kkanuthu@eng.jkuat.ac.ke; email 2 : girungu@jkuat.ac.ke). distribution systems' network reconfiguration is one way through which the bus voltages may be improved and the power system losses minimized [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thomson P.M. Mtonga, Keren K. Kaberere and George K. Irungu O total real power losses. In [9], an optimal network reconfiguration approach based on a hybrid of Cuckoo Search Algorithm and Grey Wolf Optimizer (CSA-GWO) was proposed and used to reconfigure the IEEE 33-and 69-bus radial distribution systems. The reconfiguration was carried out with the aim of minimizing total real power losses and bus voltage deviations.…”
Section: Introductionmentioning
confidence: 99%